Measurement of the Pitch Deviation and Tooth Ring run-out of Bevel Gear based on Laser Displacement Sensor - Qiu Lin; Song Aiping; Shen Yuhan; Peng Yun (Jixie chuandong)
In view of lacking precision measuring device for bevel gear and the cumbersome process of measuring process,a new integrated measuring device based on laser displacement sensor is developed. The composition and measurement principle of the measuring device are introduced,through the coordinate transformation of sampled data,the mathematical model of bevel gear tooth profile is obtained. The deviation between the actual tooth parameters and the theoretical value is calculated by the coordinate method,the pitch tolerance and the radial run-out of tooth ring are obtained. The measuring process can be simplified and the efficiency and precision can be improved by this method,the method can also be applied to the precision measurement of other cylindrical gear.